Perancangan Aplikasi Sistem Survei Karyawan di PT Uni-Charm Indonesia Berbasis Web - Meiniarti Meiniarti; Rini Malfiany; Neni Marliansih; Rahmat Gunawan (LPPM UBHINUS MALANG, 2022)
Employee Survey Information System at PT Uni Charm Indonesia Web-Based can be used as solution to full fill employee survey at PT Uni Charm Indonesia. With the existence of this information system can facilitate the employees fill out survey form and company in processing report result of survey. In this research, discuss about how to design application of employee survey system at PT Uni Charm Indonesia web-based. The system development methodology used is System Development Life Cycle (SDLC) Waterfall model which includes stages of System Analysis, Design, Encoding, Testing system. The system used using PHP programming language, database server using phpMyAdmin. The results achieved from this research is a web-based employee information survey information system. his employee survey system can assist HRD in the process of conducting annual employee surveys and facilitate employees in completing surveys so as to minimize paper use and more efficient data storage and accurate processing of survey results.